Reactivity Descriptors for Cu Bis-Phenanthroline Catalysts for the Hydrogen Peroxide Reduction Reaction - Zagal-Moya, J; Zagal-Moya, J (Elsevier Ltd, 2020)
Following previous studies where the metal-centered redox potentials of MN4 complexes are proposed as a reactivity descriptor for different electrochemical reactions, in the present work we expand this idea to a series of substituted Cu(I)-phenanthrolines adsorbed on glassy carbon electrodes as catalysts for the hydrogen peroxide reduction reaction (HPRR) in aqueous media. As the foot of the wave for HPRR on Cu-based modified electrodes is closely related to the Cu(II)/Cu(I) formal potential, we have found a linear correlation between the catalytic activity expressed as (log i)E and the E° Cu(II)/Cu(I) redox potential of the complexes with a slope (dE°/dlogi)E close to +0.120 V dec−1, showing that the catalytic activity increases with the shift of E° Cu(II)/Cu(I) to more positive potentials as a result of the electron-withdrawing nature of the substituents on the ligands. Moreover, the theoretical differences in the calculated chemical potentials (Δμ) of the reactive species follow a similar trend with the E° Cu(II)/Cu(I) where a positive shift of this parameter is related with a higher Δμ and in consequence, with high catalytic activity. Furthermore, this strategy can be used for the smart design of biosensors as it was shown by the electroanalytical results. © 2020